A variable current-limit control scheme for a bi-directional converter used in ultracapacitor applications - Ahmadi, Behzad; Barati, Farhad; Karimi, Charif (Taylor & Francis, 2018)
In ultracapacitor applications, generally, a bi-directional converter is connected to a DC bus and is designed to compensate rapid load variations on the bus. During transient phases, overloaded DC bus can push the converter out of its operating limits. For providing the necessary power, converters should be put in parallel, while each converter is limited into its optimal operating range. In a boost converter, this operating limit can be related to the inductor current and UC voltage. In this study, a variable current-limit is proposed for inductor current which then determines the operating range of the boost converter. This method will provide stability of the converter during overload transients. An experimental setup consisting of a bidirectional converter, a controllable load/source, and an ultracapacitor is presented, to validate the proposed method. Several scenarii are applied to analyze the performance of the system in overloaded phases and theoretical and experimental results are presented.